Evaluation of an adapted Certified Tobacco Treatment Specialist (CTTS) program for physicians in the Republic of Macedonia - Kaljee, Linda M; Plum, Aleksander; Holm, Amanda; Dimitrievska, Deska; Zdraveska, Marija; Spasovski, Mome; Asovski, Zoran; Redzepi, Arben; Pop Trajkova Lazarevska, Magdalena; Simoff, Michael (ECRONICON open acesss, 2025)
An estimated at 47% of adult men and 27% of women use tobacco in the Republic of Macedonia. Few policies and programs exist within the country to support tobacco dependence treatment. An adapted Certified Tobacco Treatment Specialist (aCTTS) program for physicians was implemented and evaluated to determine if participation increased knowledge and positive perceptions of clinic-based tobacco dependence treatment and counselling. In 2017, 97 physicians participated in the two-day aCTTS training. Program evaluation included a longitudinal survey at baseline and 6- and 12-months post-intervention, weekly logbooks on tobacco counselling activities, and qualitative interviews on program implementation. Outcomes data demonstrate sustained increases in knowledge at 6- (p<0.001) and 12 months (p<0.001) post-intervention and confidence to engage in counselling and treatment practices at 6- (p<0.009) and 12-months (p<0.001). Participants also decreased personal tobacco use. Logbook data indicate that participating physicians counselled 74.8% of patients with tobacco-related conditions over the 12-month evaluation period. Qualitative interview data support evaluation and logbook data on program outcomes and implementation. The aCTTS program evaluation demonstrates the potential for clinical physicians and other health care providers as mediators and supporters of tobacco cessation in the Republic of Macedonia.
Keywords: Sertified Tobaco Treatment Specialist (STTS); Physicians; Republic of North Macedonia